2010
DOI: 10.1016/j.nbd.2010.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Motor uncoordination and neuropathology in a transgenic mouse model of Machado–Joseph disease lacking intranuclear inclusions and ataxin-3 cleavage products

Abstract: Machado-Joseph disease (MJD) is a late-onset neurodegenerative disorder caused by a polyglutamine (polyQ) expansion in the ataxin-3 protein. We generated two transgenic mouse lineages expressing the expanded human ataxin-3 under the control of the CMV promoter: CMVMJD83 and CMVMJD94, carrying Q83 and Q94 stretches, respectively. Behavioral analysis revealed that the CMVMJD94 transgenic mice developed motor uncoordination, intergenerational instability of the CAG repeat and a tissue-specific increase in the som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 49 publications
3
80
0
1
Order By: Relevance
“…All the comparisons for the genotype factor were performed between CMVMJD135 mice and wild-type littermates since it has been previously shown that transgenic mice expressing human ataxin-3 carrying a normal CAG repeat tract did not display any differences in the phenotype or neuropathology in comparison with wild-type (wt) [27][28][29][30]. In addition, our previous data have shown that even expression of ataxin-3 with 83 glutamines under the CMV promoter caused no phenotype change [31].…”
Section: Cmvmjd135 Mice Express the Expanded Human Ataxin-3 In The Cnsmentioning
confidence: 99%
“…All the comparisons for the genotype factor were performed between CMVMJD135 mice and wild-type littermates since it has been previously shown that transgenic mice expressing human ataxin-3 carrying a normal CAG repeat tract did not display any differences in the phenotype or neuropathology in comparison with wild-type (wt) [27][28][29][30]. In addition, our previous data have shown that even expression of ataxin-3 with 83 glutamines under the CMV promoter caused no phenotype change [31].…”
Section: Cmvmjd135 Mice Express the Expanded Human Ataxin-3 In The Cnsmentioning
confidence: 99%
“…This fragment was not detected in non-neuronal tissue in model 2 [42]. Such a fragment was not detected in the brain of mouse models with intermediate (model 1, [32]) or low severity phenotype (model 7, [38]). The fragment is probably present in the brain of intermediate and low severity mouse models, but at levels that are not readily detectable, as observed in the brain of Q71-B heterozygous transgenic mice [33].…”
Section: Discussionmentioning
confidence: 99%
“…For each of the next 7 transgenic mice generated [32][33][34][35][36][37][38]: the transgenic mouse construct, behavior/signs, and pathology are summarized as follows.…”
Section: Mouse Modelsmentioning
confidence: 99%
See 2 more Smart Citations